Perkembangan Kedudukan Hukum (Legal Standing) Dalam Pengujian Administratif Di Pengadilan Tata Usaha Negara Dan Uji Materi Di Mahkamah Agung - Madril, Oce; Hasinanda, Jery (Jurnal Hukum & Pembangunan, 2021)
Legal standing is one of the most important aspect accordance citizen legal protection from government act which is general or concrete . In implementation at Indonesia, there are many changes in the legal standing rule. Nevertheless, this changes of rule is considered not to clarify related legal standing aspect that has impact to citizen who are having trouble for access to justice through Administratif Judicial at Administratif Court and Judicial Review at Supreme Court. Plus, the emergence of many judge decision from Administrative Court and Supreme Court Judge that sometimes expanding the meaning of legal standing, but sometimes restricting the meaning of legal standing